Relation of giant right atrial mass and thrombocytopenia; Recovery with surgery - Roghayeh Pourkia; Sadegh Sedaghat; Hamid Reza Vafaei; Seyed Sina Taheri Otaghsare (Journal of Cardiovascular and Thoracic Research)
As we know, cardiac myxoma is one of the most primary cardiac masses but laboratory findings in this type of tumor is non-specific and the diagnosis is by imaging. In this case we have reported a 61 year old man came to the emergency ward of hospital with history of recent onset dyspnea and The Laboratory finding indicates polycythemia with thrombocytopenia. Ultrasonography of abdomen and bone marrow aspiration and biopsy revealed no significant diagnosis but on echocardiography a large sized mass was detected in right atrium. After cardiologist and cardiac surgeon consultation the plan was to surgical Excision and after that the thrombocytopenia has been resolved. In this case report we want to write about a rare correlation between cardiac myxoma and thrombocytopenia and show that early diagnosis and treatment of the disease can help and totally cure complaints of patient.